2018
DOI: 10.1016/j.jval.2018.04.755
|View full text |Cite
|
Sign up to set email alerts
|

New Estimates of the Willingness-to-Pay for a Statistical Life Year: A Systematic Review of the Empirical Economic Literature

Abstract: S111and 67.0% in daily injectables. ConCluSionS: The results demonstrate how medication non-adherence rates and reasons vary across different conditions, modes, and frequencies. This underscores the potential importance and utility of using a self-reported scale to develop interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The following results are reported using the derived probabilities of diagnosis considering a lower‐ and higher‐prevalence scenarios respectively. Results pertaining to the UK were converted from pounds to euros for comparison 82 . Total economic costs of diagnosed NASH were estimated to range between €1234 and 2037 M (France), €3654 and 10 321 M (Germany), €696 and 1788 M (Italy), €435 and 724 M (Spain) and €2530 and 4676 M (UK).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following results are reported using the derived probabilities of diagnosis considering a lower‐ and higher‐prevalence scenarios respectively. Results pertaining to the UK were converted from pounds to euros for comparison 82 . Total economic costs of diagnosed NASH were estimated to range between €1234 and 2037 M (France), €3654 and 10 321 M (Germany), €696 and 1788 M (Italy), €435 and 724 M (Spain) and €2530 and 4676 M (UK).…”
Section: Resultsmentioning
confidence: 99%
“…The VSLY is an estimate of the value society places on an anonymous life. A per person VSLY for each of the five European countries was obtained from government published sources, or literature, and inflated where required 81‐83 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For an older cohort of people older than 50, a maximum value of 9.56 for the GDP multiple at age 54 can be calculated from the Aldy and Viscusi’s data [ 1 ]. A recent review of 133 estimates in the literature on VSLY found a median value of €164,000, mapping on a GDP multiple of more than 6 [ 39 ]. Thus, while the VSLY values that we elicited look large, they certainly fall within the range of values observed in other studies using different methodology and different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the original theory implies that the threshold is the highest cost-effectiveness ratio [23], the researchers instead took the mean across areas, weighting more efficient practice areas higher. A recent systematic review of 120 empirical economic studies, reporting estimates of the value of a statistical life-year using a variety of approaches, found the median to be nearly US $200,000 among European studies, and even higher among American studies [24, 25].
Fig.
…”
Section: Stay the Course—‘efficiency First’ As Exemplified By Nationmentioning
confidence: 99%